SISTEM PREDIKSI PRODUKSI PADI DI PROVINSI JAWA TIMUR MENGGUNAKAN EXPONENTIAL SMOOTHING BERBASIS WEB - Libasut Taqwa , Nungqi; Kadek Dwi Nuryana , I; Andriani , Anita (Inovate, 2019)
Most of the population of East Java Province works in the agriculture sector. One of the main agriculturalproducts produced in East Java is rice. Nearly 39.29% of the population of East Java who live in regenciesor cities depend on rice as their main livelihood. Rice is a strategic commodity because it is needed as themain source of calories. So that availability is always met, careful planning is needed. One way to controlrice production is by forecasting. In this article, forecasting of production in East Java Province is carriedout using the Exponential Smoothing method implemented on a website. Exponential Smoothing Method isone of the forecasting methods that utilizes time series data that provides exponential weighting of pastdata. Errors in forecasting are calculated using MAD, MSE, and MAPE. The data used are rice productionfrom 29 regencies and 6 cities in East Java in 2007 - 2017. The system created gives good results. Forexample for Jombang Regency, in 2018 it is predicted to produce 442,618 tons of rice with forecast errorsfor MAD, MSE, and MAPE of 44.39 each; 18.29; and 16.68%.Keywords: Exponential Smoothing, Rice, MAD, MSE, MAPE. .